Mobile-Based Transportation Vehicle for Commuter in Metro Manila (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
With the growing economy of the countries across the globe, innovation is inevitable in a fast-changing world. Asia’s fast-growing financial stability is evidence that cybernation should be more competitive globally in finances and commerce. The Philippines, which is the rising tiger of Asia, is preparing to gear-up and boost its economy through computerization. The government is pushing all its efforts to make all agencies adhere to the computerization processes by which the standard is set internationally. Our method was descriptive qualitative where we survey people using mobile-based transportation to determine what they prefer, whether conventional or mobile-based transportation. Conventional mode of transportation is our usual day-to-day trip, and mobile-based transportation is the use of apps like Grab. Given that it is modern, we have a lot to discover; we can get to where we want to be. If you ride conventionally, then you will have to wait for the vehicles.
Keywords: mobile-based transport vehicle